LPA Brief no. 10. The role of credit in the uptake and productivity of improved dairy technologies in sub-Saharan Africa - Freeman, H.A.; Jabbar, M.A.; Ehui, Simeon K. (International Livestock Research Institute, 1998)
In Ethiopia and Kenya, a unit of credit given to a credit-constrained farmer has twice as much effect on agricultural productivity as a unit of credit given to a farmer with adequate access to financial resources, according to a recent ILRI study. The study also found that giving farmers agricultural training can significantly increase farm productivity, but only if the farm is not facing a credit constraint. The study looked at both the supply of credit from financial institutions in Ethiopia, Nigeria and Uganda, particularly the bank's credit allocation policies, and at demand for credit in households in the same three countries plus Kenya. The household-level study examined the effects of credit on uptake of improved dairy technology, particularly improved cows and better feeding, in smallholder dairying.